If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b = -22 + -9b Solving 2b = -22 + -9b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '9b' to each side of the equation. 2b + 9b = -22 + -9b + 9b Combine like terms: 2b + 9b = 11b 11b = -22 + -9b + 9b Combine like terms: -9b + 9b = 0 11b = -22 + 0 11b = -22 Divide each side by '11'. b = -2 Simplifying b = -2
| 4x+8=45 | | 2x-3(4x+1)=9 | | 11x-35=24x-31 | | [x+3]=15 | | a+b+4c=12 | | 2p+4.5=5.1 | | -3c+8=-7 | | 5x+2+7x=62 | | -9x+4X-3+7= | | x+.22x=5000 | | 8+5x^2=-3x | | y=-x^2+5x+8 | | 260=10q+n | | 3x+6=2x+17 | | 3k-7=21 | | 4v-7=13 | | 12x-9=8x+27 | | 2.5x=5x | | 7-8x=3x+15 | | sqrt(3x+1)-2=6 | | 2(3x-4)=#x+1 | | 2x+22=4x | | (120-85)=x | | 8x-8=8x-1 | | 20-g=-19+2g | | 45x=9x^2 | | 0=-10y-2x | | x/507+6-6=715 | | -16x^2+68x+4=20 | | 20-12n+20=-20-2n | | -x^2+15x-56=0 | | 3b+2a=22 |